Colloquia familiaria aetate litterarum renatarum scripta ne spernamus! - Tunberg, Terentius (Nordlit, 2014)
We hope to bring to the attention of modern readers a genre of works composed in great numbers during the Renaissance, which were designed to complement the practice of conversational Latin. We single out these particular texts, because, in our opinion, teachers of Latin in our own time can still find them useful. They take the form of simple dialogues which are usually brief. They are typically called colloquia, and are filled with pure and idiomatic Latin phrases pertaining to daily life. The most famous humanists of the sixteenth and seventeenth centuries, including Erasmus, Vives, Corderius, Sturmius, Pontanus among others, are numbered among the authors of colloquia. We hope to outline the main features of these texts, to explain why they were published in such large numbers in the humanistic age, and what benefits students and teachers of Latin today can gain from such colloquia.
Keywords: Bonae litterae; Colloquium; Dialogus; Eloquentia; Familiaris (sermo); Sermo cottidianus; Sermocinari; Studia humanitatis